Pandangan Al-Quran Dalam Politik - Makmur Makmur (Institut Agama Islam Negeri Bengkulu, 2019)
Al-Quran is the word of Allah Almighty which was revealed to mankind as a source of guidance to the most straight and blessed path, the arrival of the Koran to regulate, direct, and guide human affairs towards a successful and existent world, so that there is no one any problems that exist above the world and even the hereafter unless it is regulated by the guidance of the Koran, not least in politics, even long before the creation of nature there are already political and ethical foundations that must be obeyed in healthy politics in the style of the Koran. It is not like the suspicion of sentiments towards Islam which says that Islam only takes care of the afterlife, or the expression of a group of phobias with Islamic law which says that political affairs must be separated from religious affairs, whereas worldly problems are dealt with by reason, logic and sheer lust. . So whoever holds fast to the political ethics of the Quran, he will be saved in his career towards Allah, on the contrary if he defies it will be misled and get the wrath of the owner of the universe.